2013
DOI: 10.4137/ccrep.s11903
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Differentiation of Essential Tremor and Parkinson's Disease

Abstract: We present clinical features and tremor characterization in a patient with Parkinson's disease (PD) as well as in two cases of essential tremor (ET) with some parkinsonian features but no evidence of dopaminergic terminal loss on 123 I-FP-CIT Single Photon Emission Computed Tomography (SPECT). Relatively slow frequency rest tremor and bilateral upper extremity bradykinesia without decrementing amplitude were observed in the ET cases, with unilaterally decreased arm swing in case 3. Alternating rest tremor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 15 publications
1
19
1
Order By: Relevance
“…RET differs from the postural tremor that is present in PD while a posture is maintained . As both the frequency and muscle contraction pattern are similar in RET and resting tremor, it has been suggested that RET is a variant of resting tremor .…”
Section: Introductionmentioning
confidence: 99%
“…RET differs from the postural tremor that is present in PD while a posture is maintained . As both the frequency and muscle contraction pattern are similar in RET and resting tremor, it has been suggested that RET is a variant of resting tremor .…”
Section: Introductionmentioning
confidence: 99%
“…The authors defined this tremor as "re-emergent tremor" (RET) and suggested that RET might be a possible clinical variant of RT [6]. This hypothesis was based on the observation that the two tremors share similar frequency characteristics [6,7] and a similar asynchronous muscle activation pattern [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Belvisi et al, [5] observed that the severity of non-motor symptoms was also similar in the two groups of patients. Previous accelerometric [1,11] and electromyographic recordings [12] have shown that both the frequency (about 4.5-5.5 Hz) and the asynchronous pattern of antagonistic muscle activation [6,12] are similar in RET and resting tremor. The severity of RET positively correlates with that of resting tremor in PD patients on treatment [5].…”
mentioning
confidence: 93%
“…In PD, RET usually involves the upper limbs [1,[4][5][6] and is bilateral in 50% of cases [5]. Recent clinical reports have described patients with PD with RET even in the jaw [7] and tongue [8,9].…”
mentioning
confidence: 99%